PhD Thesis in Public International Law: The 2018 Agreement to Prevent Unregulated High Seas Fisheries in the Central Arctic Ocean : Its Background, Motivations and Aspirations (Abstract) - Lena Johanna, Zahner (University of Lapland, 2019)
publishedVersion